Dietary inflammatory index, genetic susceptibility and risk of incident dementia: a prospective cohort study from UK biobank - Peng, Min; Yuan, Shiqi; Lu, Dan; Ling, Yitong; Huang, Xiaxuan; Lyu, Jun; Xu, Anding (Journal of neurology, 2024)
Background Genetic factors, diet and inflammation are associated with the development of dementia. In this study, we aimed at evaluating the impact of the dietary inflammatory index (DII) scores and genetic susceptibility on the development of dementia. Methods This prospective study involved 207,301 participants aged between 39 and 72 years from UK biobank. A web-based 24-h dietary questionnaire was collected at least once from participants between 2006 and 2012. The DII was calculated based on inflammatory effect score of nutrients. Individual AD-GRS (Alzheimer’s disease genetic risk score) was calculated. Incident dementia was ascertained through hospital or death records. Results Of all 207,301 participants, 468 incident cases of all-cause dementia (165 AD, 91 VD and 26 FTD) were reported during a follow-up period of 11.4 years. The participants in the highest quintile (Q) of DII scores reported a higher risk for all-cause dementia (Q5 vs. Q3, hazard ratio (HR) = 1.702; 95% CI: 1.285–2.255) and VD (Q5 vs. Q3, HR = 2.266, 95% CI: 1.133–4.531) compared to participants in the Q3. Besides, when compared with the Q1, there was a higher risk for AD in the subjects of Q5 (Q5 vs. Q1, HR = 1.590; 95% CI: 1.004–2.519). There was a non-linear relationship between DII score and all-cause incidence ( P for non-linear = 0.038) by restricted cubic splines. Subgroup analysis found that the increased risk for all-cause dementia and AD was more pronounced in the elderly, women, and higher educated population. Cox regression models indicated that compared with the participants who had a low AD-GRS risk and in the lowest tertile of DII, participants had a high AD-GRS and the highest tertile of DII were associated with a higher risk of AD (HR = 1.757, 95% CI: 1.082–2.855, P = 0.023). Conclusions The DII scores were independently associated with an augmented risk for all-cause dementia, AD and VD. Additionally, high AD-GRS with higher DII scores was significantly associated with a higher risk of AD.